The Effect of Servıce Qualıty on Revısıt Intentıon Wıth sWord Of Mouth Medıatıon Varıables and Tourıst Satısfactıon - Edna Raisa Naibaho; Oda Ignatius Besar Hariyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Service quality plays an important role in influencing travel decisions and tourist intentions to visit the same destination, in the future. This study was conducted with the aim of analyzing and knowing how the influence of the service quality variable on the intention to revisit with the mediating variable word of mouth and visitor satisfaction. The dependent variable of this study is the intention to visit again. The independent variable of this research is service quality, the mediating variable of this research is word of mouth and visitor satisfaction. The research method used is quantitative in nature, on the grounds that research on the effect of quality on satisfaction, return intention and service requires data in numerical form to build hypotheses that are related to the phenomenon to be studied and exploration. The sample at the research site is one of the travel agents. in Jambi City, using 200 respondents, and testing data using SPSS. The results showed that the service quality variable had a significant positive relationship on visitor satisfaction. The service quality variable has a positive significant relationship on word of mouth, the visitor satisfaction variable has a positive significant relationship on word of mouth, the service quality variable has a positive significant relationship on the intention to return, the visitor satisfaction variable has a positive significant relationship on the intention to return, the word variable of mouth has a significant positive relationship on the revisit intention, the variable of visitor satisfaction is able to mediate the relationship between service quality and revisit intention.